Penurunan Kadar COD dan TSS dengan Menggunakan Teknik Pipe Filter Layer pada Limbah Industri Keripik Singkong - Siti Fatimah; Najmudin A. Mumtaz; Nur Hidayati (Politeknosains, 2016)
Cassava contains hydrocyanic acid (HCN) derived from the hydrolysis process cyanogenic glucoside (linamarin and lotaustralin) by endogenous enzymes that are marked in blue on cassava. Production of cassava chips contained in Donohudan, Surakarta very abundant with a turnover of 10 tons each month so that the production process produces some waste that has no economic value. Wastewater from the washing of cassava chips can be a serious problem if not treated properly. Mechanical installation of pipe filter layer may be one alternative to resolve these problems .. This technique uses a combination of natural adsorbent with terraced flowed into the pipe. The adsorbent used include gravel, sepet (coconut fiber), silica sand, zeolite. The parameters examined in this study is the analysis of the levels of COD (Chemical Oxygen Demand) and TSS (Total Solid Suspended) in the wastewater industry cassava chips. Data collection was performed by calculating the COD and TSS levels before and after processing with pipe filter layer. Based on data obtained optimum pH value accordance with the standard of food waste that is 7.89. For COD and TSS, the optimum value changes occurred on respectively of 99.5% and 99.7%. Mechanical pipe filter layer effectively handle the wastewater industry cassava chips